OPTIMASI PENGKOMPOSAN LIMBAH SAYURAN PASAR MINGGU SEBAGAI SUMBER PUPUK ORGANIK - Tri Waluyo (Jurnal Ilmu dan Budaya, 2020)
Jakarta produces garbage around 6000-6500 tons consisting of organic and non organic waste. The percentage of organic waste arround 55% of the total waste. Composting using local microorganism as activator is expected to reduce waste volume. The purpose of this research is to analyze kind of local microorganism to acceleratethe decomposition of organic matter of vegetable waste; analyzing local microorganism concentration on accelerate of decomposition of organic matter of vegetable waste; analyzed the interaction between type of local microorganism and concentration of local microorganismon the acceleration of decomposition of organic matter. The experiments were arranged in a Factorial Randomized Completely Block Design (RCBD), which consisted of three typesof local microorganism (Tape, snail and banana) withthree level concentration (450 ML, 600 ML, 750 ML) treated divided into three blocks as replicates. The results showed that: The highest temperature (35.5oC) was in the 12th day, the composting process was not achieved thermophilic temperature. Local microorganism from banana culm at 450 ML dosage accelerated the weight loss of organic matter (17.69%), the most refined texture, highest phosphorus (0.49%) and potassium (1.47%) higher than the other treatments. Banana local microorganism spinach at a dose of 600 ML showed the highest levels of calcium (1.28%), carbon content (12.45%), magnesium (1.30%) and reduced C/N ratio to lowest 6.03 compared with the other treatments. Banana local microorganism at 750 ML doseshowed a darker compost color (dark brown).